HUWE1 interacts with PCNA to alleviate replication stress. (4th May 2016) - Choe, Katherine N; Nicolae, Claudia M; Constantin, Daniel; Imamura Kawasawa, Yuka; Delgado‐Diaz, Maria Rocio; De, Subhajyoti; Freire, Raimundo; Smits, Veronique AJ; Moldovan, George‐Lucian
Abstract: Defects in DNA replication, DNA damage response, and DNA repair compromise genomic stability and promote cancer development. In particular, unrepaired DNA lesions can arrest the progression of the DNA replication machinery during S‐phase, causing replication stress, mutations, and DNA breaks. HUWE1 is a HECT‐type ubiquitin ligase that targets proteins involved in cell fate, survival, and differentiation. Here, we report that HUWE1 is essential for genomic stability, by promoting replication of damaged DNA. We show that HUWE1‐knockout cells are unable to mitigate replication stress, resulting in replication defects and DNA breakage. Importantly, we find that this novel role of HUWE1 requires its interaction with the replication factor PCNA, a master regulator of replication fork restart, at stalled replication forks. Finally, we provide evidence that HUWE1 mono‐ubiquitinates H2AX to promote signaling at stalled forks. Altogether, our work identifies HUWE1 as a novel regulator of the replication stress response. Synopsis: The HUWE1 ubiquitin ligase is recruited to stalled replication forks by the replication factor PCNA. HUWE1 ubiquitinates H2AX to promote restart of stalled replication forks and mitigate replication stress. HUWE1 contains a PCNA interacting domain (PIP‐box) required for PCNA interaction. HUWE1‐knockout cells show increased replication stress, which can be corrected by re‐expression of wild‐type but not PCNA interaction‐deficient HUWE1 mutant. HUWE1 mono‐ubiquitinates H2AX to promote γH2AX signaling, recruitment of repair proteins, and restart of stalled replication forks. Abstract : The HUWE1 ubiquitin ligase is recruited to stalled replication forks by the replication factor PCNA. HUWE1 ubiquitinates H2AX to promote restart of stalled replication forks and mitigate replication stress.